DISTRIBUTION OF SEDIMENT, BENTHIC FORAMINIFERA AND MERCURY IN THE SOUTH YATSUSHIRO SEA, KYUSHU, JAPAN - R. Rifardi (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Bottom sediment samples were collected at 74 stations in the South Yatsushiro Sea, off the west coast of central Kyushu Island, Japan using gravity corer. 62 core samples were used for bottom sediments analysis and for determination of mercury content. Among these samples, only 5 core samples were used for this study in an attempt to clarify the relationship between the vertical distributions of benthic foraminiferal assemblages (Bulimina denudata) and mercury contents in core sediments. The distribution pattern of sediment median diameter and of the maximum mercury content at some layers of each core show that the fine-grained sediment polluted by mercury were transported both northeastward and southward by weak longshore currents and spread toward north and west across the northern and souhtern part of the South Yatsushiro Sea. Bulimina denudata shows the highest frequency at every layer which has high mercury content ranging from 0.14 to 3.46 ppm, and is comparatively low at all unpolluted layers. The frequency of Bulimina denudata slightly decreased at the layers showing more than 3 ppm. All these signals suggest that Bulimina denudata does not prefer the bottom sediments showing high mercury contents but tolerates mercury pollution.